Evaluating Online Phone Swap Transactions Under Sharia Economic Law in Manado - Jamal, Ridwan; Azzochrah, Nurul Azizah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2024)
In recent years, the proliferation of online transactions has extended into diverse markets, including the mobile phone swap market. This study investigates the compatibility of such transactions with Sharia economic law, using Tuminting, Indonesia, as a case study. The research employed a qualitative approach, incorporating interviews and observations to gather data from participants engaged in online phone swap transactions. Key findings indicate that while these transactions provide convenience and accessibility, they raise significant concerns regarding compliance with Sharia principles, particularly in terms of economic justice and transaction transparency. The study proposes a framework for enhancing Sharia compliance in online swap transactions, suggesting modifications in transaction structures and regulatory oversight. This research contributes to the understanding of digital market dynamics in Islamic finance, offering insights for consumers, practitioners, and policymakers striving for ethical economic practices in digital transactions.